2015
DOI: 10.1515/aicue-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Of A Fast-Growing Firm’s Profits: Empirical Evidence For Slovenia

Abstract: This paper seeks to explain the relationship between a firm’s profitability and firm size, leverage ratio and labour costs – using a sample of 782 Slovenian fast-growing firms from the years 2008 and 2009. We determined that profitability is negatively related to the firm size and leverage ratio, but positively to the labour costs. These results illustrate that, with increasing firm size, a fast-growing firm becomes less profitable. The negative coefficient for the leverage ratio indicates that the higher the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
0
4
1
2
Order By: Relevance
“…Generally, our results in terms of size are similar to those of Majumdar (1997) for India; Pervan and Mlikota (2013) for Croatia; Nunes and Serrasqueiro (2015) and Nunes et al (2009) for Portugal, Yazdanfar (2013) for Sweden, Andres (2008) for Germany, and Asimakopoulo et al (2009) for Greece. However, these results contradict those of Goddard et al (2005) for Belgium, Spain, Italy, France, and the UK, Močnik and Širec (2015) for Slovenia, Hunjra et al (2014) for Pakistan, and Saito (2008) for Japan.…”
Section: Resultsmentioning
confidence: 77%
“…Generally, our results in terms of size are similar to those of Majumdar (1997) for India; Pervan and Mlikota (2013) for Croatia; Nunes and Serrasqueiro (2015) and Nunes et al (2009) for Portugal, Yazdanfar (2013) for Sweden, Andres (2008) for Germany, and Asimakopoulo et al (2009) for Greece. However, these results contradict those of Goddard et al (2005) for Belgium, Spain, Italy, France, and the UK, Močnik and Širec (2015) for Slovenia, Hunjra et al (2014) for Pakistan, and Saito (2008) for Japan.…”
Section: Resultsmentioning
confidence: 77%
“…Peningkatan utang perusahaan akan berimbas pada menurunnya solvabilitas perusahaan yang kemudian akan berakibat pada menurunnya return saham yang akan diperoleh (Purwitajati, 2016). Penggunaan modal sendiri untuk membiayai perusahaan akan memangkas beban tetap akibat utang sehingga dapat meningkatkan profitabilitas perusahaan (Mocnik & Sirec, 2015). Utang jangka panjang maupun utang jangka pendek dapat mengurangi kinerja perusahaan, apabila utang perusahaan jumlahnya lebih besar dari total modal perusahaan maka kinerja perusahaan tidak akan berjalan baik sehingga manajer perlu memperhitungkan dengan baik proporsi leverage perusahaan (Awais, et al, 2016).…”
Section: Pendahuluanunclassified
“…However, other research found a negative or weak negative association between size and firm performance. For instance (Močnik & Širec, 2015)and (Banchuenvijit & Pariyanont, 2012) shed light on the factors like firm size, that determines the profitability of a developing company using a sample of 782 Slovenian fast-growing companies. The result from the findings showed a negative association between firm company and profitability.…”
Section: 6-firm Size and Firm Performancementioning
confidence: 99%